Civic Conscience, the True Educational Ideal in John Dewey and Jean Piaget - Irina Siminiceanu (Babes-Bolyai University, 2024)
In a world heavily challenged by new historical and technological developments, the civic conscience of the individual must regain a defining importance in the education process. As the culmination of efforts to shape the new generations, it reinstates democratic values in schools, so that we can find them later in society. Here, I will illustrate that two great philosophers of education, John Dewey and Jean Piaget, have already shown that educational systems should primarily aim towards civic conscience, even though neither of them uses the term explicitly. New solutions must be sought to reintegrate society into schools as an educational material, to foster the development of the skills that the citizen of tomorrow will need, a citizen who will not only have the mission to restore balance but also to ensure the progress of society.